Biodegradable film as well as preparation method and application thereof
The biodegradable membrane with a four-layer composite structure design solves the problem of balancing transparency, barrier properties and processing adaptability in existing technologies, and achieves a biodegradable membrane with high transparency, excellent barrier properties and stable processing performance, which is suitable for food, daily necessities and pharmaceutical packaging.
Patent Information
- Application Number
- CN202511319019.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-16
- Publication Date
- 2025-12-19
AI Technical Summary
Existing biodegradable films struggle to balance transparency, barrier properties, processing adaptability, and degradability, failing to meet the demands for high transparency, excellent barrier properties, and stable processing performance in food, daily necessities, and pharmaceutical packaging.
It adopts a four-layer composite structure design, including a heat-sealing layer, a core substrate layer, a barrier layer, and a scratch-resistant coating, which are respectively composed of amorphous polylactic acid, semi-crystalline polylactic acid, ethylene-vinyl alcohol copolymer, and waterborne polyurethane. Through precise synergistic design, it achieves high transparency, excellent barrier properties, and stable processing performance.
It achieves environmental friendliness with a biodegradability rate of ≥90%, high transparency with a haze of ≤3%, excellent barrier properties with an oxygen permeability of ≤50cc/(m2·day·atm) and a water vapor permeability of ≤5g/(m2·day·atm), and stable processability with a heat-sealing strength of ≥3kgf/15mm, making it suitable for high-speed packaging production lines.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of packaging technology, specifically relating to a biodegradable film, its preparation method, and its uses. Technical Background
[0002] With increasing environmental awareness, the problems of traditional non-biodegradable plastic films (such as OPP and PET) are becoming increasingly prominent due to their difficulty in natural decomposition and their tendency to cause environmental pollution. Their application in visual packaging sectors such as food and daily necessities, where clear display of product information is required, is severely limited. While biodegradable films made from a single material can currently address environmental issues, they suffer from the following key drawbacks:
[0003] Insufficient transparency: Single biodegradable materials or traditional multi-layer biodegradable structures generally have a haze exceeding 8% due to poor interlayer compatibility and the addition of plasticizers, which cannot meet the requirements of visual packaging for clear product display.
[0004] Poor barrier properties: Most biodegradable films have weak barrier properties against oxygen and water vapor, making it difficult to protect products inside the packaging that are easily oxidized or absorb moisture.
[0005] Low processing adaptability: Existing biodegradable films have unstable heat shrinkage rate and insufficient heat sealing strength, which can easily lead to problems such as wrinkles and poor sealing in high-speed packaging production lines;
[0006] Imbalance between degradation efficiency and durability: Some biodegradable membranes sacrifice mechanical properties in pursuit of rapid degradation, making them prone to damage during transportation and storage.
[0007] The present invention is proposed to solve the above problems. Summary of the Invention
[0008] This invention proposes a composite biodegradable membrane. Through a multi-layer structure design of "core substrate layer + functional coating", it achieves high biodegradability while synergistically providing high transparency, excellent barrier properties and stable processing performance, thus meeting the needs of packaging boxes for food, daily necessities or pharmaceutical products.
[0009] The technical solution of the present invention is as follows:
[0010] The first aspect of this invention discloses a biodegradable membrane, which has a four-layer composite structure, consisting of a heat-sealing layer, a core substrate layer, a barrier layer, and a scratch-resistant coating from the inside out; the biodegradable membrane has a 60-day biodegradation rate of ≥90%, a haze of ≤3%, and an oxygen permeability of ≤50cc / (m²). 2 • day • atm), water vapor transmission rate ≤ 5 g / (m 2 Heat sealing strength ≥3 kgf / 15 mm, heat shrinkage rate 4-6% and longitudinal and transverse shrinkage difference <0.5%.
[0011] Preferably, the thickness of the biodegradable membrane is 18.5-34 μm; wherein the thickness of the heat-sealing layer is 1-3 μm, the thickness of the core substrate layer is 15-25 μm, the thickness of the barrier layer is 2-5 μm, and the thickness of the scratch-resistant coating is 0.5-1 μm.
[0012] Preferably, the raw material of the heat-sealing layer includes the following components in parts by weight: 90-95 parts of amorphous polylactic acid (a-PLA), 5-10 parts of ethylene-vinyl acetate copolymer (EVA), and 0.5-1 parts of slip agent;
[0013] The raw materials of the core substrate layer include the following components in parts by weight: 70-90 parts of semi-crystalline polylactic acid (sc-PLA), 10-30 parts of polyhydroxyalkanoate (PHA), and 0.1-0.5 parts of antioxidant;
[0014] The raw material of the barrier layer includes the following components in parts by weight: 95-99 parts of ethylene-vinyl alcohol copolymer (EVOH), 1-5 parts of nanocellulose, and 0.1-0.3 parts of dispersant;
[0015] The raw materials for the anti-scratch coating include the following components in parts by weight: 95-98 parts of waterborne polyurethane (WPU), 2-5 parts of silica nanoparticles, and 0.5-1 parts of crosslinking agent.
[0016] Preferably, the polyhydroxyalkanoate (PHA) is a copolymer of 3-hydroxybutyrate and 4-hydroxybutyrate, wherein the molar percentage of 4-hydroxybutyrate units is 10%-20%.
[0017] Preferably, the slip agent is a mixture of erucamide and oleamide in a weight ratio of 1:1; the antioxidant is a hindered phenolic antioxidant; the dispersant is polyethylene glycol; and the crosslinking agent is isocyanate.
[0018] Preferably, the nanocellulose has an average diameter of 50-100 nm and a length of 1-5 μm.
[0019] Preferably, the scratch-resistant coating has a pencil hardness ≥2H and a water contact angle ≤60°.
[0020] The second aspect of this invention discloses a method for preparing the biodegradable membrane, comprising the following steps:
[0021] (1) Preparation of core substrate layer: Semi-crystalline polylactic acid, polyhydroxyalkanoate and antioxidant are mixed evenly and melt-blended in a twin-screw extruder at 170-190℃. The mixture is then extruded and cast through a T-die, and the temperature of the cooling roller is controlled at 20-25℃ to obtain a core substrate layer with a thickness of 15-25μm.
[0022] (2) Preparation of barrier layer: Ethylene-vinyl alcohol copolymer (EVOH), nanocellulose and dispersant are dissolved in N,N-dimethylformamide (DMF), mixed evenly and then coated on one side of the core substrate layer by a doctor blade, and dried at 80-100℃ for 10-15 min to form a barrier layer with a thickness of 2-5 μm.
[0023] (3) Preparation of heat-sealing layer: Amorphous polylactic acid (a-PLA), ethylene-vinyl acetate copolymer (EVA) and slip agent are mixed evenly and melted in a single screw extruder at 160-180℃. The mixture is then bonded to the other side of the core substrate layer through an extrusion composite process and cooled to form a heat-sealing layer with a thickness of 1-3μm.
[0024] (4) Preparation of anti-scratch coating: Waterborne polyurethane (WPU), silica nanoparticles and crosslinking agent are mixed evenly and coated on the surface of the barrier layer by microgravure. The mixture is cured at 60-80℃ for 20-30 min to form an anti-scratch coating with a thickness of 0.5-1μm.
[0025] (5) Biaxial stretching and shaping: The four-layer composite film is stretched 2.5-3 times in a longitudinal stretching machine at 60-70℃, then stretched 3-3.5 times in a transverse stretching machine at 80-90℃, and finally heat-set at 110-120℃ for 5-10 minutes, and then wound up to obtain the biodegradable film.
[0026] Preferably, the screw speed of the twin-screw extruder in step (1) is 150-200 rpm; and the bonding pressure in step (3) is 0.3-0.5 MPa.
[0027] The third aspect of this invention discloses the use of the biodegradable film for packaging boxes of food, daily necessities or pharmaceutical products.
[0028] The biodegradable membrane of the present invention adopts a four-layer composite structure design of "heat-sealing layer - core substrate layer - barrier layer - scratch-resistant coating". Through the precise synergy of the components and functions of each layer, it comprehensively solves the problem of the difficulty in balancing transparency, barrier properties, mechanical properties, processability and degradability of existing biodegradable membranes.
[0029] The composition and function of the four-layer structure are as follows:
[0030] Heat-sealing layer: This layer uses amorphous polylactic acid (a-PLA) as the main material (90-95 parts by weight), giving the film good thermal tack. The addition of ethylene-vinyl acetate copolymer (EVA) (5-10 parts by weight) aims to improve the heat-sealing flowability and sealing reliability of a-PLA, ensuring a strong and uniform seal under high-speed packaging conditions. The addition of a slip agent (0.5-1 parts by weight) effectively reduces the coefficient of friction on the film surface, preventing adhesion during production and packaging, and significantly improving its adaptability to automated high-speed production lines. The thickness of this layer is controlled at 1-3 μm to minimize the impact on overall transparency while ensuring effective heat sealing.
[0031] Core substrate layer: Serving as the main mechanical support for the film, this layer is composed of a blend of semi-crystalline polylactic acid (sc-PLA) (70-90 parts by weight) and polyhydroxyalkanoate (PHA) (10-30 parts by weight). sc-PLA provides high tensile strength (≥25MPa) and rigidity; while PHA, especially 3-hydroxybutyrate-4-hydroxybutyrate copolymer (P(3HB-co-4HB)), effectively improves the brittleness of pure PLA, increasing the elongation at break to ≥50%, enhancing the film's flexibility and impact resistance. The blending of these two materials in a specific ratio achieves a balance between excellent mechanical properties and high transparency. A small amount of antioxidant (0.1-0.5 parts by weight) is used to ensure material stability during processing. This layer, with a thickness of 15-25μm, is the core component constituting the film's thickness and mechanical properties.
[0032] Barrier Layer: This layer primarily blocks the permeation of external oxygen and water vapor to protect the contents. Its main component is ethylene-vinyl alcohol copolymer (EVOH) (95-99 parts by weight), which inherently possesses excellent oxygen barrier properties. The addition of nanocellulose (1-5 parts by weight, average diameter 50-100 nm, length 1-5 μm) and a dispersant (0.1-0.3 parts by weight) not only further reduces water vapor permeability by utilizing the inherent barrier properties of nanocellulose but also enhances the interfacial bonding with EVOH and the core substrate layer through its nano-effect, effectively preventing interlayer delamination. This layer is formed using a solution coating method, with its thickness precisely controlled at 2-5 μm, providing excellent barrier performance while having minimal impact on light transmission.
[0033] Scratch-resistant coating: As the outermost layer of the film, its main function is to protect the printed pattern and the film itself, preventing scratches from affecting the product's appearance and information identification during transportation, stacking, and shelving. This layer uses waterborne polyurethane (WPU) (95-98 parts by weight) as the film-forming material, which is environmentally friendly and non-toxic. The addition of silica nanoparticles (2-5 parts by weight) as a reinforcing phase significantly improves the surface hardness and abrasion resistance of the coating, achieving a pencil hardness of ≥2H. The addition of a crosslinking agent (0.5-1 parts by weight) promotes the crosslinking and curing of the WPU, forming a dense and robust coating network. This layer is extremely thin (0.5-1 μm) and modified to have a water contact angle ≤60°, combining scratch resistance with moderate surface energy, which is beneficial for subsequent printing and palletizing stability.
[0034] Through the meticulous design of the aforementioned multilayer structure and components, this invention achieves synergistic control of the following key performance characteristics:
[0035] Biodegradability Control: The main structure of the film (heat-sealing layer, core substrate layer) is made of biodegradable polymers (PLA, PHA, EVA). The barrier layer EVOH also undergoes slow degradation in a composting environment. The outermost scratch-resistant coating is a water-based system, free of solvent pollution, and extremely thin, thus not significantly hindering the overall biodegradation process. Through the optimal selection and proportioning of materials in each layer, the biodegradability rate of the film is ensured to be ≥90% within 60 days, achieving a balance between functional use and end-of-life environmental friendliness.
[0036] High transparency is achieved by precisely controlling the refractive indices of each layer (sc-PLA ~1.45, PHA ~1.46, EVOH ~1.49) to ensure interlayer refractive index matching, minimizing light scattering at multilayer interfaces. Simultaneously, optimized processing techniques (such as biaxial stretching) eliminate visible defects within and between layers, successfully controlling the overall haze of the film to ≤3%, meeting the stringent requirements of clear display of the contents in packaging.
[0037] Excellent Barrier Properties: The EVOH in the barrier layer provides intrinsically high oxygen barrier properties. The addition of nanocellulose creates a tortuous permeation pathway within the EVOH matrix, and its numerous hydroxyl groups can bind to water molecules, synergistically enhancing the barrier capacity against water vapor. Ultimately, this results in an oxygen permeability of the film ≤50cc / (m²). 2 • day • atm), water vapor transmission rate ≤ 5 g / (m 2 (·day·atm), which can effectively extend the shelf life of environmentally sensitive products such as food and cigarettes.
[0038] Stable processability and mechanical properties are guaranteed: The blend of sc-PLA and PHA in the core substrate layer lays the foundation for the film's high strength, with a heat-sealing strength ≥3kgf / 15mm. Finally, the biaxial stretching process further improves the orientation and crystallinity of the molecular chains, giving the film excellent and stable dimensional properties. The heat shrinkage rate is controlled at 4-6%, and the difference between longitudinal and transverse shrinkage is <0.5%, effectively preventing warping and wrinkling after packaging. The optimized heat-sealing layer formulation ensures high heat-sealing strength.
[0039] The beneficial effects of the present invention.
[0040] The biodegradable membrane of the present invention has the following beneficial effects:
[0041] 1. Environmental friendliness and visibility go hand in hand: Biodegradability rate ≥90% in 60 days, completely replacing traditional non-biodegradable films; at the same time, haze ≤3%, meeting the packaging requirements for product display and solving the industry pain point of "environmental protection and transparency cannot be achieved at the same time".
[0042] 2. Excellent barrier properties: The oxygen and water vapor permeability is much lower than that of existing biodegradable membranes, making it suitable for packaging products that are sensitive to storage environment, such as baked goods and precision daily necessities.
[0043] 3. High processing adaptability: Stable heat shrinkage rate and high heat sealing strength, which can be adapted to high-speed packaging production lines, reduce packaging defect rate and reduce enterprise production costs.
[0044] 4. High durability: The scratch-resistant coating has a pencil hardness of ≥2H, preventing scratches on the film surface during transportation; the core substrate layer has a tensile strength of ≥25MPa, excellent tear resistance, and reduces the risk of packaging damage.
[0045] 5. Environmentally friendly preparation process: It adopts green processes such as water-based coating and melt blending, with no organic solvent volatilization, which meets the requirements of clean production and is easy to scale up industrially. Detailed Implementation
[0046] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without inventive effort are within the scope of protection of this invention.
[0047] Unless otherwise stated, the percentages in this application are percentages by mass.
[0048] Example 1: Preparation of biodegradable membrane and its application in cigarette pack packaging
[0049] 1. Application Background
[0050] As the smallest sales unit that directly contacts consumers, cigarette pack packaging not only needs to possess good sealing, moisture resistance, and scratch resistance, but also excellent transparency and environmental friendliness to meet modern consumers' dual demands for product visibility and sustainability. Traditional cigarette pack outer films mostly use biaxially oriented polypropylene (BOPP) or polyethylene (PE) films, which, while offering high transparency and good processing performance, are not biodegradable and easily cause environmental pollution after disposal. With increasing global efforts to control tobacco use and stricter environmental regulations, developing a packaging film that meets the requirements of high transparency, high barrier properties, and good biodegradability has become an urgent industry need.
[0051] 2. Analysis of the compatibility between thin film structure and performance
[0052] The four-layer composite biodegradable film (heat-sealing layer / core substrate layer / barrier layer / scratch-resistant coating) used in this embodiment exhibits excellent overall performance in cigarette pack packaging:
[0053] High transparency and aesthetics: Haze ≤3%, far lower than traditional biodegradable film, close to the transparency of BOPP, can clearly display cigarette box printed patterns, brand logos and anti-counterfeiting labels, enhancing product grade and consumer purchasing desire.
[0054] Excellent barrier properties: oxygen permeability ≤50cc / (m 2 • day • atm), water vapor transmission rate ≤ 5 g / (m 2 It has a shelf life of atm (2 days) and can effectively block the intrusion of external oxygen and moisture, preventing tobacco from getting damp, moldy, or losing its aroma, thus extending its shelf life by at least 30%. It is especially suitable for high-end cigarette products, which are extremely sensitive to the storage environment.
[0055] Excellent heat-sealing and processability: heat-sealing strength ≥3kgf / 15mm, heat shrinkage rate controlled at 4-6% and directional difference <0.5%, suitable for high-speed cigarette packaging machines, with smooth and wrinkle-free sealing and no air leakage, significantly reducing downtime and scrap rates.
[0056] Scratch resistance and durability: The scratch-resistant coating has a pencil hardness of ≥2H, which can effectively resist friction and scratches during transportation and shelving, keep the film surface smooth, and avoid affecting the appearance and barcode recognition due to scratches.
[0057] Fully degradable and environmentally friendly: Biodegradability ≥90% within 60 days, in compliance with ISO 14855-1 standards. After disposal, it can be completely decomposed in an industrial composting environment with no microplastic residue, which aligns with the tobacco industry's development strategy.
[0058] 3. Specific application solutions
[0059] Material selection:
[0060] The four-layer structure thin film of the present invention is used, wherein:
[0061] Heat-sealing layer: a-PLA + 8% EVA + 0.8% slip agent (erucamide / oleamide 1:1), 2μm thick, ensuring low-temperature heat-sealing and slip properties;
[0062] Core substrate layer: sc-PLA and PHA (3HB-co-4HB, 4-HB content 15%) are blended in an 8:2 ratio, with a thickness of 20μm, providing mechanical support and flexibility; the antioxidant is 0.2% tocopheryl acetate;
[0063] Barrier layer: EVOH (94%) + nanocellulose (3%, diameter 80nm, length 3μm) + dispersant PEG400 (polyethylene glycol 400), thickness 3μm, coated on one side of the core layer;
[0064] Scratch-resistant coating: WPU + 3% silica nanoparticles + crosslinking agent HDI (hexamethylene diisocyanate; 1,6-Diisocyanatohexane, HDI), 0.8μm thick, coated on the outside of the barrier layer.
[0065] Preparation process:
[0066] (1) Preparation of core substrate layer: Semi-crystalline polylactic acid, polyhydroxyalkanoate and antioxidant are mixed evenly, melt-blended in a twin-screw extruder at 180°C, and extruded and cast through a T-die. The temperature of the cooling roller is controlled at 20°C to obtain a core substrate layer with a thickness of 20μm.
[0067] (2) Preparation of barrier layer: Ethylene-vinyl alcohol copolymer (EVOH), nanocellulose and dispersant are dissolved in N,N-dimethylformamide (DMF), mixed evenly and then coated on one side of the core substrate layer by a doctor blade, and dried at 80°C for 10 min to form a barrier layer with a thickness of 3 μm.
[0068] (3) Preparation of heat-sealing layer: Amorphous polylactic acid (a-PLA), ethylene-vinyl acetate copolymer (EVA) and slip agent are mixed evenly and melted in a single screw extruder at 160°C. The mixture is then bonded to the other side of the core substrate layer through an extrusion composite process and cooled to form a heat-sealing layer with a thickness of 2μm.
[0069] (4) Preparation of anti-scratch coating: Waterborne polyurethane (WPU), silica nanoparticles and crosslinking agent are mixed evenly and coated on the surface of the barrier layer by microgravure. The mixture is cured at 60°C for 20 min to form an anti-scratch coating with a thickness of 0.8 μm.
[0070] (5) Biaxial stretching and setting: The four-layer composite film is stretched 2.8 times in a longitudinal stretching machine at 65°C, then stretched 3.2 times in a transverse stretching machine at 85°C, and finally heat-set at 110°C for 5 minutes, and then wound up to obtain the biodegradable film. The biaxial stretching process is the key control to ensure dimensional stability and low shrinkage difference.
[0071] Packaging equipment compatibility:
[0072] It is suitable for high-speed cigarette packaging machines such as Focke and Sasib, and requires no equipment modification.
[0073] 4. Effect Verification
[0074] After a pilot application by a certain tobacco company, the film performed as follows in the packaging of a certain brand of cigarette packs:
[0075] Appearance: High transparency, the gold lettering and red background of the cigarette box are clearly visible, with no glare or fogging;
[0076] Sealing performance: Average heat seal strength 3.5 kgf / 15 mm, no air leakage, no curling edges;
[0077] Barrier properties: After 30 days of accelerated aging test (40℃ / 75%RH), the moisture content of the tobacco remained almost unchanged;
[0078] Mechanical properties: tensile strength 28MPa, elongation at break 55%, superior to traditional PLA film;
[0079] Degradability: Industrial compost loses 92% of its weight after 60 days, indicating complete degradation with no residue;
[0080] 5. Conclusion
[0081] The biodegradable film of this embodiment has been successfully applied to cigarette pack packaging. While maintaining high transparency, high barrier properties and good processability, it achieves the goal of full degradation and environmental protection. It can serve as an ideal alternative to BOPP and help the tobacco industry achieve green transformation.
[0082] Example 2: Preparation of biodegradable membrane and its application in cigarette carton packaging
[0083] 1. Application Background
[0084] As the outer packaging for multiple cartons of cigarettes, cigarette carton packaging needs to possess higher mechanical strength, compression resistance, impact resistance, and environmental adaptability, while also meeting brand display and environmental protection requirements. Traditional carton packaging often uses PET / PE composite film or BOPP pearlescent film; although these offer high strength and good gloss, they are not biodegradable and are difficult to recycle. The biodegradable film in this embodiment, through structural optimization and performance improvement, also performs excellently in carton packaging.
[0085] 2. Thin film structure and performance enhancement design
[0086] To address the higher requirements for mechanical properties and compression resistance in carton packaging, the film was optimized as follows based on Example 1:
[0087] Increase the thickness of the core substrate layer: Increase the thickness of the core layer from 20μm to 25μm, and adjust the ratio of sc-PLA to PHA to 7:3 to further improve tensile strength and puncture resistance.
[0088] Enhanced moisture resistance of the barrier layer: The content of nanocellulose in the EVOH / nanocellulose layer is increased to 5%, which enhances the barrier stability of this film in high humidity environments.
[0089] Enhanced scratch-resistant coating: The amount of silica added to the scratch-resistant coating is increased to 5%; the pencil hardness can reach 3H, making it more suitable for stacking and transporting cartons during logistics.
[0090] Heat seal layer adaptability adjustment: The heat seal layer thickness is increased to 3μm, and the EVA addition is 10%, which improves the adaptability of the heat seal range (it can be used for cold sealing or heat sealing processes).
[0091] 3. Specific application scheme, based on the adjustment of Example 1.
[0092] Material configuration:
[0093] Heat-sealing layer: a-PLA + 10% EVA + 1% slip agent, 3μm thickness;
[0094] Core substrate layer: sc-PLA:PHA = 7:3, thickness 25μm;
[0095] Barrier layer: EVOH + 5% nanocellulose, 4μm thick;
[0096] Scratch-resistant coating: WPU + 5% SiO2, 1μm thickness.
[0097] Preparation process: Adjusted based on Example 1.
[0098] Biaxial stretching and setting steps: The biaxial stretching process was adjusted to 3 times the longitudinal temperature at 70°C and 3.5 times the transverse temperature at 90°C, with a heat setting temperature of 120°C for 8 minutes; this improved dimensional stability and mechanical properties. Other steps were the same as in Example 1.
[0099] Packaging applications: Suitable for carton packaging lines, heat sealing temperature 135–140℃, pressure 0.5MPa, line speed 200 pieces / minute.
[0100] 4. Effect Verification
[0101] Actual packaging and transportation tests were conducted at a tobacco logistics center.
[0102] Compression resistance: The empty box has a compression strength of 350N, which is higher than the 300N of BOPP / PET composite film.
[0103] Impact resistance: No breakage was observed during the drop ball impact test (500g steel ball at a height of 50cm).
[0104] Environmental adaptability: After 10 cycles of testing from -5℃ to 50℃, the membrane showed no deformation or delamination.
[0105] Printability: Can be printed with water-based inks, adhesion 5B (ASTM D3359).
[0106] Degradation performance: The 60-day compost degradation rate is 91%, which meets expectations.
[0107] 5. Conclusion
[0108] The biodegradable film of this embodiment exhibits excellent mechanical properties, environmental adaptability, and fully degradable characteristics in cigarette carton packaging, and can completely replace traditional plastic composite films; it is suitable for the outer packaging needs of high-end cigarette brands and has significant environmental and market value.
[0109] The above embodiments are described in detail, but they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.
Claims
1. A biodegradable membrane, characterized in that, The biodegradable membrane has a four-layer composite structure, consisting of a heat-sealing layer, a core substrate layer, a barrier layer, and a scratch-resistant coating from the inside out. The biodegradable membrane exhibits a 60-day biodegradation rate ≥90%, a haze ≤3%, and an oxygen permeability ≤50cc / (m²). 2 • day • atm), water vapor transmission rate ≤ 5 g / (m 2 Heat sealing strength ≥3 kgf / 15 mm, heat shrinkage rate 4-6% and longitudinal and transverse shrinkage difference <0.5%.
2. The biodegradable membrane according to claim 1, characterized in that, The biodegradable membrane has a thickness of 18.5-34 μm; wherein the heat-sealing layer has a thickness of 1-3 μm, the core substrate layer has a thickness of 15-25 μm, the barrier layer has a thickness of 2-5 μm, and the scratch-resistant coating has a thickness of 0.5-1 μm.
3. The biodegradable membrane according to claim 1, characterized in that, The raw materials of the heat-sealing layer include the following components in parts by weight: 90-95 parts of amorphous polylactic acid, 5-10 parts of ethylene-vinyl acetate copolymer, and 0.5-1 parts of slip agent; the raw materials of the core substrate layer include the following components in parts by weight: 70-90 parts of semi-crystalline polylactic acid, 10-30 parts of polyhydroxyalkanoate, and 0.1-0.5 parts of antioxidant; the raw materials of the barrier layer include the following components in parts by weight: 95-99 parts of ethylene-vinyl alcohol copolymer, 1-5 parts of nanocellulose, and 0.1-0.3 parts of dispersant; the raw materials of the scratch-resistant coating include the following components in parts by weight: 95-98 parts of waterborne polyurethane, 2-5 parts of silica nanoparticles, and 0.5-1 parts of crosslinking agent.
4. The biodegradable membrane according to claim 3, characterized in that, The polyhydroxyalkanoate is a copolymer of 3-hydroxybutyrate and 4-hydroxybutyrate, wherein the molar percentage of 4-hydroxybutyrate units is 10%-20%.
5. The biodegradable membrane according to claim 3, characterized in that, The slip agent is a mixture of erucamide and oleamide in a weight ratio of 1:1; the antioxidant is a hindered phenolic antioxidant; the dispersant is polyethylene glycol; and the crosslinking agent is isocyanate.
6. The biodegradable membrane according to claim 3, characterized in that, The nanocellulose has an average diameter of 50-100 nm and a length of 1-5 μm.
7. The biodegradable membrane according to claim 3, characterized in that, The scratch-resistant coating has a pencil hardness ≥2H and a water contact angle ≤60°.
8. A method for preparing a biodegradable membrane according to any one of claims 1 to 7, characterized in that, Includes the following steps: (1) Preparation of core substrate layer: Semi-crystalline polylactic acid, polyhydroxyalkanoate and antioxidant are mixed evenly and melt-blended in a twin-screw extruder at 170-190℃. The mixture is then extruded and cast through a T-die, and the temperature of the cooling roller is controlled at 20-25℃ to obtain a core substrate layer with a thickness of 15-25μm. (2) Preparation of barrier layer: Ethylene-vinyl alcohol copolymer, nanocellulose and dispersant are dissolved in N,N-dimethylformamide, mixed evenly and then coated on one side of the core substrate layer by a doctor blade, and dried at 80-100℃ for 10-15min to form a barrier layer with a thickness of 2-5μm. (3) Preparation of heat-sealing layer: Amorphous polylactic acid, ethylene-vinyl acetate copolymer and slip agent are mixed evenly and melted in a single screw extruder at 160-180℃. The mixture is then bonded to the other side of the core substrate layer through an extrusion composite process. After cooling, a heat-sealing layer with a thickness of 1-3μm is formed. (4) Preparation of anti-scratch coating: water-based polyurethane, silica nanoparticles and crosslinking agent are mixed evenly and coated on the surface of the barrier layer by microgravure. The mixture is cured at 60-80℃ for 20-30 min to form an anti-scratch coating with a thickness of 0.5-1μm. (5) Biaxial stretching and shaping: The four-layer composite film is stretched 2.5-3 times in a longitudinal stretching machine at 60-70℃, then stretched 3-3.5 times in a transverse stretching machine at 80-90℃, and finally heat-set at 110-120℃ for 5-10 minutes and then wound up to obtain the biodegradable film.
9. The preparation method according to claim 8, characterized in that, The screw speed of the twin-screw extruder in step (1) is 150-200 rpm; the bonding pressure in step (3) is 0.3-0.5 MPa.
10. The use of the biodegradable film according to any one of claims 1 to 7 for packaging boxes of food, daily necessities or pharmaceutical products.
